Between Old and New Needs: The Issue of Inclusion of the Elderly before, during and after COVID-19. The Case of Rural Areas in Canada-Québec and Italy - Alberio, Marco; Plachesi, Rebecca (Revue Interventions économiques / Papers in Political Economy, 2024)
During the health crisis, the elderly were identified as being among those most at risk of developing complications in the event of contamination by the virus, so in Italy, Canada and many other parts of the world, various specific measures were implemented to protect them. However, these have mainly involved measures to reduce both physical and social contact. This has led to repercussions not only on the social and psychological well-being of seniors but also on their social participation and inclusion. According to these aspects, in this article we analyze the situations and experiences of the elderly (aged seventy and over) in rural areas, in Italy and Canada, trying to highlight the socio-territorial effects of this health crisis on seniors. Therefore, on one hand, the aim is to identify the aspects that have accentuated the vulnerability of seniors and, on the other hand, the protective and supportive measures that have enabled them to cope with the pandemic crisis and its consequences. Furthermore, we will illustrate the different efforts to respond to the complex issue of ageing (demographic dimension) within rural areas (socio-territorial dimension) in an emergency-pandemic context (socio-health dimension), asking whether or not the initiatives and processes implemented by a variety of actors (non-profit associations, local or public institutions) respond to the needs and requirements of seniors living (in) the areas under study.